Quercetin Impact in Pancreatic Cancer: An Overview on Its Therapeutic Effects. (3rd November 2021) - Asgharian, Parina; Tazehkand, Abbas Pirpour; Soofiyani, Saiedeh Razi; Hosseini, Kamran; Martorell, Miquel; Tarhriz, Vahideh; Ahangari, Hossein; Cruz-Martins, Natália; Sharifi-Rad, Javad; Almarhoon, Zainab M.; Ydyrys, Alibek; Nurzhanyat, Ablaikhanova; et al.
Abstract : Pancreatic cancer (PC) is a lethal malignancy cancer, and its mortality rates have been increasing worldwide. Diagnosis of this cancer is complicated, as it does not often present symptoms, and most patients present an irremediable tumor having a 5-year survival rate after diagnosis. Regarding treatment, many concerns have also been raised, as most tumors are found at advanced stages. At present, anticancer compounds-rich foods have been utilized to control PC. Among such bioactive molecules, flavonoid compounds have shown excellent anticancer abilities, such as quercetin, which has been used as an adjunctive or alternative drug to PC treatment by inhibitory or stimulatory biological mechanisms including autophagy, apoptosis, cell growth reduction or inhibition, EMT, oxidative stress, and enhancing sensitivity to chemotherapy agents. The recognition that this natural product has beneficial effects on cancer treatment has boosted the researchers' interest towards more extensive studies to use herbal medicine for anticancer purposes. In addition, due to the expensive cost and high rate of side effects of anticancer drugs, attempts have been made to use quercetin but also other flavonoids for preventing and treating PC. Based on related studies, it has been found that the quercetin compound has significant effect on cancerous cell lines as well as animal models. Therefore, it can be used as a supplementary drug to treat a variety of cancers, particularly pancreatic cancer. This review is aimed at discussing the therapeutic effects of quercetin by targeting the molecular signaling pathway and identifying antigrowth, cell proliferation, antioxidative stress, EMT, induction of apoptotic, and autophagic features.